2016
DOI: 10.3390/ijerph13111139
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Arrhythmia and Helicobacter pylori Infection: A Meta-Analysis of Case-Control Studies

Abstract: Arrhythmia is a common disease around the world and Helicobacter pylori (H. pylori) is a bacterium infecting 28% to 84% of subjects, depending on the population tested. However, the implication of H. pylori in cardiac arrhythmia is poorly understood. We performed this meta-analysis with an aim to identify the association between arrhythmia and H. pylori. We searched PubMed, Embase, Web of Science, and the Cochrane library databases to select studies on the association between arrhythmia and H. pylori. In the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Overall, 3036 articles that met our search criteria were first identified from the seven databases. Sixty articles9–18 27–76 of observational studies were finally selected, covering 88 unique outcomes (figure 1). Fifty-four meta-analyses10–17 28–34 38–40 42–44 47–50 54–60 64–70 72–75 were reanalysed because they did not present all of the results of estimates (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, 3036 articles that met our search criteria were first identified from the seven databases. Sixty articles9–18 27–76 of observational studies were finally selected, covering 88 unique outcomes (figure 1). Fifty-four meta-analyses10–17 28–34 38–40 42–44 47–50 54–60 64–70 72–75 were reanalysed because they did not present all of the results of estimates (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…No association with Increase risk of Decrease risk of Europe Cholangiocarcinoma, 14 colorectal, cancer, 75 diabetes mellitus, 39 diabetic nephropathy, 56 alcoholic cirrhosis, 33 Parkinson's disease 50 Barrett's oesophagus 32 Arrhythmia, 65 asthma, 16 biliary lithiasis, 73 migraine, 52 recurrent aphthous stomatitis, 40 chronic urticaria 34…”
Section: Associations Between H Pylori Infection and Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…91,92 However, a meta-analysis of six studies observed no association between H. pylori infection and AF, though they did report significant publication bias. 93…”
Section: Alcoholic Liver Diseasementioning
confidence: 99%